Linear Behavior of the Phase Lifetime in Frequency-Domain Fluorescence Lifetime Imaging of FRET Constructs - Sumetsky, Daniel; Jiang, James Y.; Ayad, Marina A.; Mahon, Timothy; Menaesse, Audrey; Cararo-Lopes, Marina M.; Patel, Mihir V.; Firestein, Bonnie L.; Boustany, Nada N. (Frontiers in Physics, 2021)
We utilize a cost-effective frequency-domain fluorescence lifetime imaging microscope to measure the phase lifetime of mTFP1 in mTFP1-mVenus fluorescence resonance energy transfer (FRET) constructs relevant to the VinTS molecular tension probe. Our data were collected at 15 modulation frequencies ω/2π selected between 14 and 70 MHz. The lifetime of mTFP1 was τ_D= 3.11 +/- 0.02 ns in the absence of acceptor. For modulation frequencies, ω, such that (ω∙τ_D )<1.1, the phase lifetime of mTFP1in the presence of acceptor (mVenus) , τ_ϕ^DA, was directly related to the amplitude-weighted lifetime τ_ave^DA inferred from the known FRET efficiency (EFRETtrue) of the constructs. A linear fit to a plot of (ω∙τ_ϕ^DA ) vs.(ω∙τ_ave^DA ) yielded a slope of 0.79+/-0.05 and intercept of 0.095+/-0.029 (R2= 0.952). Thus, our results suggest that a linear relationship exists between the apparent EFRETapp based on the measured phase lifetime and EFRETtrue for frequencies such that (ω∙τ_D )<1.1. We had previously reported a similar relationship between EFRETapp and EFRETtrue at 42 MHz. Our current results provide additional evidence in support of this observation, but further investigation is still required to fully characterize these results. A direct relationship between τ_ϕ^DAand τ_ave^DA has the potential to simplify significantly data acquisition and interpretation in fluorescence lifetime measurements of FRET constructs.